Az átalakulás társadalmi költségei - Kemény, István (Szociológiai Szemle, 2024)
The primary assumption of this treatise is that the social costs that have been incurred and augmented since 1990 are not the consequeences of the transformation of the old socie-economic system, but of its total collapse. This assumption is demonstrated by the examples of the issues of unemployment and the pensions. A further argument is provided by referring to the fact that later, when the market economy has already been consolidated, the social ills do not disappear automatically. The concluding part of the treatise questions the widespread belief according to which the social costs are too high and it also calls into question the assumption that these costs can be reduced in the near future.